KONSTITUSIONALITAS PENGATURAN DEKONSENTRASI DALAM PASAL 5 AYAT (4) UNDANG-UNDANG NOMOR 23 TAHUN 2014 TENTANG PEMERINTAHAN DAERAH DIKAITKAN DENGAN PASAL 18 AYAT (2) UNDANG-UNDANG DASAR NEGARA REPUBLIK INDONESIA TAHUN 1945 - IskandarIskandarIskandar, Hafiz; Haryono, Dodi; Artina, Dessy (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
In a unitary State can use the system sentralistis or desentralistis in this Country Indonesia chose the United State desentralistis, it can be seen in chapter VI of the Constitution of the Republic of Indonesia in 1945 About local governance, in the formulation of article 18 paragraph (2) of the constitution of 1945. Another thing in Act No. 23 of 2014 on local governance as implementing Article 18, which lists the dekonsentrasi between the principle of autonomy and medebewind tasks. Then arose the question of whether the dekonsentrasi settings are not set in the Constitution 1945 can be arranged in the Act that in fact is the advanced settings over the constitution of 1945.The type of research that used the author is normative legal research. Normative legal research legal research which is doctrinal, also referred to as the research library or study emphasis is focused on documentary skunder data. The technique of data collection in this research is the study of librarianship, namely authors take an excerpt from the book, literature, or the supporting books relating to issues that will be examined. In the writing of this thesis, the author uses descriptive analysis (descriptive analisys) that aims to provide the task force on the subject of the research based on data obtained from the subject researched.The results of this thesis research States Country Indonesia is a unitary State desentralistik, it can be seen in the history of local government in Indonesia which is reviewed from before independence and the aftermath of independence, To anticipate it and then the Government implement political decentralization and deconsentrasition together in a big way, it is aimed at opening opportunities to the population to participate in organising and taking care of the interests of his household. Actually it doesn't include the word "deconsentrasition" in article 18 paragraph (2) of the constitution of 1945 remain unconstitutional according to the author, as long as deconsentrasition is meant as part of a decentralization commonly referred to as ambtelijk i.e. pelimpahan decentralisatie authority of State equipment (Center) to subordinate agencies (region) to carry out certain jobs in the Government.Keywords: Constitutionality – Deconsentrasi – Local Governance